Star-shaped poly[2-(dimethylamino)ethyl methacrylate] and its derivatives: toward new properties and applications - Plamper, F. A.; Synatschke, Ch. V.; Majewski, A. P.; Schmalz, A.; Schmalz, H.; Müller, A. H. E. (Polimery, 2014)
The versatility of polymer and hybrid systems containing the polycation PDMAEMA, especially in the star-shaped topology, is reviewed. Different complexation schemes are addressed, including the use of stimuli-responsive counterions. This leads to the use of PDMAEMA stars for nucleotide transfection or advanced hydrogel formulations.